FAVA-Based Community Service Program to Strengthen Teachers' Capacity in Developing Curriculum-Aligned Plastic-Waste Mathematics Learning Media: Evidence from Gresik, Indonesia - Ekowati, Dyah Worowirastri; Ismail, Agung Deddiliawan (Universitas Muhammadiyah Malang, 2026)
This community service program aims to overcome environmental and educational challenges in Gresik, where limited waste management and the use of plastic waste in mathematics learning media in secondary schools have not been implemented. Based on discussions with MGMP Mathematics SMA Gresik Regency, two main gaps were found: (1) the absence of a program to develop plastic-based mathematics learning media, and (2) the lack of assistance to support teachers in the production and implementation of these media. This program aims to provide sustainable assistance to teachers in creating environmentally friendly plastic waste-based mathematics learning media, as a contribution to local sustainability initiatives. The method used is FAVA (Focus Group Discussion, Action, Validity, Accountability) which will be held from December 2025 to February 2026. The first FGD was held at SMA Muhammadiyah 1 Gresik on December 8, 2025, involving representatives of 20 MGMP Mathematics SMA/SMK/MA Gresik. The action was carried out through offline and online mentoring to develop a prototype of learning media using common plastic waste, such as bottles and caps, for mathematics topics. The validity stage ensures clear curriculum and procedural suitability. This program produced three winners of mathematics learning media at the Gresik Regency level, strengthening teachers' capacity in contextualizing mathematics learning with environmental values.